(untitled) (Thành phố Hồ Chí Minh, 2013)
Lessons For IELTS - Reading Welcome to this New Oriental IELTS preparation course and the Reading Book in particular.IELTS, the International English language Testing System, is one of the world's most popular English language tests for entry into university or higher education .
Keywords: English language,Ngôn ngữ Anh; Reading,Đọc hiểu